UNIPOLAR DEPRESSION TO BIPOLAR DISORDER CONVERSION - Dyah Kusuma Wardhani (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Bipolar disorder cases have increased compared to a decade ago. It is thought that this increase is the result of a high number of bipolar patients who were not recognized early on because bipolar and unipolar depression is difficult to distinguish from one another. In addition, this problem also gave rise to the hypothesis that unipolar depression could develop into bipolar disorder. Therefore, the diagnosis conversion of unipolar depresion into bipolar disorder and its predictor needs to be studied further. Literature review by using several literatures between 2011-2021 that discuss about unipolar depresion, bipolar disorder, diagnosis conversion, and factors that influence the conversion of unipolar depression diagnosis into bipolar disorder. Diagnosis of unipolar depression can turn into bipolar disorder. This may be due to failure to differentiate unipolar and bipolar depressive episodes, strict diagnostic criteria, failure to recognize history of hypomania/mania, or due to the genuine progression of the disorders. This problem leads to the provision of inappropriate therapy for patients that trigger disease progression and worsen the prognosis. One of the anticipations that can be done is to explore the presence of conversion predictor factor. It includes the age of onset <25 years, bipolar family history, patientâ€™s course of depression (high recurrence, short duration, moderate to severe depression, hypersomnia, psychomotor retardation, psychosis symptoms, postpartum depression), resistance to antidepressants, antidepressant-induced hypomania/mania, and the presence of subthreshold mania. If these factors are found, the patient should be closely monitored and therapy adjustment may be required.Â Keywords: bipolar disorder, conversion, predictor, unipolar depression.